Musculoskeletal discomfort evaluation using Rapid Entire Body Assessment (REBA) and Quick Exposure Check (QEC) among woodworking workers in Selangor, Malaysia - Mohd Hawari, Nurhanisah; Sulaiman, Ruhaizin; Kamarudin, Khairul Manami; Che Me, Rosalam (Science Alert, 2022)
Background: Work-related musculoskeletal disorders (WMSDs) are one of the major occupational health problems among woodworkers, especially in developed and developing countries, such as Malaysia. Recently, numerous studies on MSDs have been widely explored, yet the culture, environment and regulatory practices on hazard and risk may differ in each country. Method: The study was conducted on 30 workers in 3 woodworking workshops in Selangor, Malaysia. Through this study, demographic surveys, QEC, and REBA were examined. Results: The results indicated that the most critical task is the lifting and assembling activity. Conclusion: These two activities may require an ergonomic intervention to reduce WMSDs risks.